A Critical Discourse Analysis of Ideology Represented in Amy Tan's The Joy Luck Club Novel - Ananda, Hairani Alfi; Kuncara, Singgih Daru; Max, Jonathan Irene Sartika Dewi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
This research is conducted to explain ideology represented through transitivity and modality in Amy Tan’s The Joy Luck Club novel. Thus, CDA is a thinking concept and approach in this research comprises three dimensions in analyzing those are description, interpretation, and explanation. As a result, the researcher reads the data and uses descriptive qualitative method finds Jing Mei Woo uses all the processes in transitivity and modality to represent her negative liberty except Lindo Jong does not use existential process only. In representing their positive liberty, Jing Mei Woo does not use existential and high process only. While, Lindo Jong does not use behavioral and existential process but uses all levels in modality process. When responding to others, Negative and Positive Liberty of Jing Mei Woo and Lindo Jong are shaped by material, mental, relational, behavioral, and verbal process. While, Negative Liberty of Jing Mei Woo is shaped by median level but for Lindo Jong by low level. Positive Liberty of Jing Mei Woo is shaped by median and high level but Lindo Jong by all of the levels in modality those are low, median, and high. In the beginning, Jing Mei Woo defends her ideology which is more colored by American than Chinese beliefs. Otherwise, Lindo Jong wants them to balance between American circumstances and Chinese characters and beliefs. To sum up, both characters face the same phase of using negative liberty before finally using positive liberty. A sequence of moment becomes lesson to them then to be wiser before feeling, thinking, behaving, deciding, saying, and finally doing action based on positive liberty.